Editor’s Essay: The Multi-Disciplinary and Diverse Field of Crisis and Risk Communication Research (Journal of International Crisis and Risk Communication Research, 2021)
The field of crisis and risk communication research has always been multidisciplinary bringing together researchers from many fields like business, public relations, political science, sociology, psychology, journalism, tourism, and public health. However, there is often a common perception outside the fields of crisis communication that is a corporate discipline focused mostly on helping organizations manage their reputations. As the pieces in this issue demonstrate, our field serves the public interest in many ways and is a growing global field of study.